Free Banking and Bank Entry in Latin America - Zegarra Basurco, Luis Felipe (CENTRUM Publishing, 2012)
This article analyzes the impact of free-banking on the banking sector in Latin America in the 19th and early 20th centuries. I use data for seven countries to compare the entry of banks and the growth of bank output prior and after the enactment of free-banking laws to determine whether free-banking (by establishing general requirements for granting note-issuance rights) lowered barriers to entry. The results show that in most Latin American countries the adoption of free-banking laws did not cause in the short run an increase in bank entry and in bank output growth.
Keywords: Latin America; Banking sector; Bank laws; Bank entry; http://purl.org/pe-repo/ocde/ford#5.02.04